Food accessibility and its influencing factors during early social restriction period of COVID-19 pandemic in Indonesia - Dewi, Novianti Tysmala; Gisca, Bernadheta; Rahmasari, Nurulita Aida; Havelaar, Shirleen Gabrielle; Ermayani, Evie; Wangge, Grace (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to assess food accessibility and its influencing factors among adults in Indonesia during the early COVID-19 pandemic. Methods: The research was cross-sectional and conducted using an online questionnaire that assessed sociodemographic characteristics, food access, physical access (enabling factors for individuals to reach food physically), financial access, social support, and coping strategies of the respondents. We included 439 adults, 358 females and 81 males, aged 20-62 years. Results: This research found that physical access difficulties (aOR=3.945; CI:1.652-9.421; p=0.002), unemployment status (aOR=3.104; CI:1.436-6.712; p=0.004), and lower education level (aOR=2.819; CI:1.036-7.672; p=0.042) were associated with increased inability to access food. Meanwhile, coping strategies for food insecurity conditions (aOR=0.634; CI:0.536-0.750; p<0.001) were protective of the inability to access food (R2=0.298). Conclusion: People with a high risk of unemployment and low education who will have difficulty accessing food in times of social restrictions should be protected.